Clontuskert Augustinian Priory, east window, mullion - O'Donovan, Danielle (My University, 2009)
Mullion of curvilinear east window. Mullion is moulded at both inner and outer faces. Inner face comprises: frontal fillet flanked at either side by hollow chamfer, quadrant, hollow chamfer. The moulding of the outer face comprises: frontal fillet flanked at either side by hollow chamfer, right-angled rebate and hollow chamfer. The sides of the mullion have glass grooves, closer to the outer face.
East window
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Augustinian; Tracery (Architecture); Late Medieval; moldings, hollow; roll moldings; mullions